2018
DOI: 10.1590/s2175-97902018000417543
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of N-arylsulfonyl-3-acylindole benzoyl hydrazone derivatives as anti-HIV-1 agents

Abstract: The discovery and development of novel inhibitors with activity against variants of human immunodeficiency virus type 1 (HIV-1) is pivotal for overcoming treatment failure. As our ongoing work on research of anti-HIV-1 inhibitors, 32 N-arylsulfonyl-3-acylindole benzoyl hydrazone derivatives were prepared by introduction of the hydrazone fragments on the N-arylsulfonyl-3-acylindolyl skeleton and preliminarily screened in vitro as HIV-1 inhibitors for the first time. Among of all the reported analogues, eight co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…[13][14][15][16][17][18][19] Several studies on the chemistry and bioactivity of N-acylhydrazone lead scaffold have been published recently. This topic has gained significance over time for the development of novel, therapeutically effective bioactive N-acylhydrazone candidates as anticancer, [20][21][22][23] anti-inflammatory, [24][25][26][27][28][29][30][31] anti-Alzheimer, [32][33][34][35] antimicrobial agents, [36][37][38][39][40] and more. N-Acylhydrazones continue to be a prominent topic in therapeutic research, especially when it comes to the treatment of cancer.…”
Section: Researchers In Medicinal Chemistry Have Paid Interest Tomentioning
confidence: 99%
“…[13][14][15][16][17][18][19] Several studies on the chemistry and bioactivity of N-acylhydrazone lead scaffold have been published recently. This topic has gained significance over time for the development of novel, therapeutically effective bioactive N-acylhydrazone candidates as anticancer, [20][21][22][23] anti-inflammatory, [24][25][26][27][28][29][30][31] anti-Alzheimer, [32][33][34][35] antimicrobial agents, [36][37][38][39][40] and more. N-Acylhydrazones continue to be a prominent topic in therapeutic research, especially when it comes to the treatment of cancer.…”
Section: Researchers In Medicinal Chemistry Have Paid Interest Tomentioning
confidence: 99%
“…The indole ring was found not only in natural compounds but also in diverse semisynthetic and synthetic drug-like molecules [ 32 , 33 ]. They exhibit antimicrobial [ 34 , 35 , 36 , 37 , 38 , 39 ], anti-inflammatory [ 40 , 41 ], COX inhibitory [ 42 , 43 ] anticancer [ 44 , 45 , 46 ], antiviral [ 47 , 48 ], anti-HIV [ 49 , 50 ], and antidiabetic [ 51 ] activities. Among the natural compounds containing the indolene fragment, several imidazoline and imidazolidine alkaloids are known, which have a wide spectrum of biological activity, including antibacterial.…”
Section: Introductionmentioning
confidence: 99%
“…They exhibit antimicrobial [34][35][36][37][38][39], anti-inflammatory [40,41], COX inhibitory [42,43] anticancer [44][45][46], antiviral [47,48], anti-HIV [49,50], and antidiabetic [51] activities. Among the natural compounds containing the indolene fragment, several imidazoline and imidazolidine alkaloids are known, which have a wide spectrum of biological activity, including antibacterial.…”
Section: Introductionmentioning
confidence: 99%
“…Dihydro-1-aryl-8-alkyl pyrazolo(3,4-b)indoles were synthesized by Mandour et al that showed remarkable anticonvulsant, analgesic, and anti-inflammatory activities in comparison to diazepam, flufenamic acid, and indomethacin as positive controls. Among the tested compounds, the most potent compounds were found to be (6-chlorocyclohexa-2,4-dienyl)(1-(2,4,6-trichlorophenyl)pyrazolo[3,4-b]indol-8(1H)-yl)methanone(39) and (6-chlorocyclohexa-2,4-dienyl)(1-phenylpyrazolo[3,4b]indol-8(1H)-yl)methanone(40) with percentage inflammation inhibition 85 and 79% (100 mg kg -1 ) and 70 and 64% ( 50 mg kg -1 ) respectively[23].2-(5-Methoxy-2-methyl-1H-indol-3-yl)-N'-[(E)-(substituted phenyl)methylidene] acetohydrazide derivatives were reported by Bhat et al and investigated for cyclooxygenase expression, lipid peroxidation, ulcerogenic, analgesic, and anti-inflammatory activities. Compound (E)-N'-(3-nitrobenzylidene)-2-(5-methoxy-2-methyl-1Hindol-3-yl) acetohydrazide(41) was active as analgesic and anti-inflammatory agents[24].Benzothiazole containing benzene sulphonamide and carboxamide were prepared by Ugwu et al and evaluated for their in vivo anti-inflammatory, analgesic, and ulcerogenic activities.…”
mentioning
confidence: 99%